Using animal history to inform current debates in gene editing farm animals: A systematic review - Wright, Will; Tworek, Heidi J. S.; von Keyserlingk, Marina A. G.; Koralesky, Katherine E.; Weary, Daniel M. (Frontiers in Sustainable Food Systems, 2022)
There is growing interest in gene editing farm animals. Some alterations could benefit animal welfare (e.g., improved heat tolerance in cattle with the “slick” gene), the environment (e.g., reducing methane emissions from cattle with induced pluripotent stem cells), and productivity (e.g., higher weight gains in cattle with the “double muscling” gene). Existing scholarship on the acceptability of such modifications has used myriad approaches to identify societal factors that shape the ethics and governance of this technology. We argue that integrating historical approaches—particularly from the relatively new and burgeoning field of animal history—offers a form of “anticipatory knowledge” that can help guide discussions on this topic. We conducted a systematic review of the animal history literature in English, German, and Spanish to identify the influence of political, scientific, economic, social, and cultural factors on the development and acceptance of such technologies. We identified analogous structures and fault lines in past debates about farm animals that provide insights for contemporary discussions about gene editing. Those analogous structures include the market power of meatpackers or the racialized precepts in livestock breeding, and fault lines, like the disconnect between states and citizens over the direction of food systems. Highlighting these similarities demonstrates how external forces have shaped—and will continue to shape—the acceptance or rejection of emerging biotechnologies as applied to farm animals.